Simulated electronic health documentation : A cross-sectional exploration of factors influencing nursing students’ intention to use - Chan, Kim Geok; Saloma, Pawi; Ong, M.F; Yanika, Kowitlawakul; Goy, Siew Ching (Elsevier Science, Ltd., 2020)
The aim of this study was to investigate factors influencing nursing students’ intention to use a simulated web application ‘Integrated Nursing Education System’ for practicing electronic health documentation. The cross sectional study was conducted at a Malaysian University that provides undergraduate nursing degree program. A total of 133 undergraduate nursing students in their year 2 to year 4 of the program were recruited. They had accessed the simulated web-application as part of the teaching-learning activities during the academic year 2016/2017. Technology Acceptance Model was used to guide the study. Validated questionnaires were used to measure the students’ perceived ease of use, perceived usefulness, attitudes and intention to use the application. Data collection was done at the end of the semester. Data analysis was done using SPSS (19.0) and AMOS (23.0). Perceived usefulness was the most influential factor of the students’ intention to use the simulated webapplication. Perceived ease of use influenced their perceived usefulness significantly. Nurse educators should explain the usefulness of the simulated web-application before assigning students to access it to practice electronic health documentation. The availability of a stable internet access and IT support is important to influence students’ perceived ease of use and intention to use the application.